Pengaruh Kualitas Pelayanan, Media Digital, Dan Promosi Terhadap Minat Menabung di Bank BTN Syariah Cabang Mataram - Jaitun Indriyati; Luluk Fadliyanti; Nadia Nuril Ferdaus (Economic Reviews Journal, 2026)
This study aims to analyze the influence of service quality, digital media, and promotion on customers’ saving interest at Bank BTN Syariah Mataram Branch. This research employed a quantitative approach with an associative research design. The population of this study consisted of 15,496 active customers of Bank BTN Syariah Mataram Branch, while the sample consisted of 100 respondents determined using the Slovin formula and purposive sampling technique. Data were collected through questionnaires, while the analysis techniques included validity test, reliability test, classical assumption test, multiple linear regression, t-test, F-test, and coefficient of determination (R²) using SPSS version 22. The results showed that partially service quality, digital media, and promotion had a positive and significant effect on saving interest. Simultaneously, these three variables also had a significant effect on saving interest. The most dominant variable affecting saving interest was digital media. The coefficient of determination indicated that variations in saving interest could be explained by service quality, digital media, and promotion, while the remaining portion was influenced by other factors outside the research model. Therefore, Bank BTN Syariah Mataram Branch is expected to continuously improve service quality, optimize the use of digital media, and strengthen promotional strategies in order to increase public interest in saving.